Pengaruh Career Planning terhadap Kesiapan Mahasisawa Mencari Kerja Studi Kasus pada Mahasiswa Kota Medan - Dini Anggaini; Disti Aulia Putri; Nirwana Sari; Wilda Dwina Br Pandia; Bayu Teta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to determine the effect of career planning on students' job readiness, using a case study of university students in Medan City. The background of this research is based on the low job readiness among students, often caused by the lack of structured career planning. This research employs a descriptive quantitative method with a sample of 35 respondents. Data analysis techniques include validity and reliability tests, normality test, heteroscedasticity test, simple linear regression, t-test, and determination test. The normality test results show that the data are normally distributed (sig. = 0.769 > 0.05). The heteroscedasticity test indicates no heteroscedasticity problem. Regression analysis results show that career planning has a significant effect on job readiness, with a significance value of 0.002 (< 0.05). The coefficient of determination (R²) is 0.250, indicating that 25% of job readiness is explained by career planning. It can be concluded that the better the career planning possessed by students, the higher their readiness to enter the job market. This study supports the importance of early career development for students.